Iron ore tailing mud-based cement admixture and preparation method thereof

By combining iron ore tail sludge with a variety of materials and preparing iron ore tail sludge-based cement mixed materials, the problems of environmental pollution and resource waste of iron ore tail sludge are solved, and the mechanical properties and resource utilization of cement are improved.

CN119613076APending Publication Date: 2025-03-14HAINAN LVFENG RESOURCES DEV CO LTD +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411843010.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Due to the small particle size and high moisture content of iron ore tailings sludge, it is easy to lead to environmental pollution and waste of resources. Traditional tailings dam storage has safety risks and land occupation problems, so it is necessary to find harmless treatment methods and improve resource utilization.

Method used

Iron ore tailing slurry is used as raw material, and iron ore tailing slurry is prepared through calcination, ultrasonic dispersion and grinding and other materials by combining composite calcium powder, water glass, polyvinyl alcohol solution, polydimethylsiloxane, calcium sulfate whiskers and silane coupling agents.

Benefits of technology

It improves the comprehensive utilization rate of iron ore tailing mud, saves resources, and at the same time enhances the compressive strength and flexural strength of cement, reducing the negative impact on cement performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188370650000061
    Figure BDA0005188370650000061
  • Figure BDA0005188370650000071
    Figure BDA0005188370650000071
Patent Text Reader

Abstract

The invention provides an iron ore tailing mud-based cement admixture and a preparation method thereof. The material comprises the following raw materials in parts by weight: 50-60 parts of tailing mud, 12-16 parts of composite calcium powder, 8-13 parts of water glass, 18-25 parts of a polyvinyl alcohol solution, 10-14 parts of polydimethylsiloxane, 20-27 parts of calcium sulfate whiskers and 12-16 parts of a silane coupling agent. The preparation method comprises the following steps: drying and crushing the iron ore tailing mud, adding the composite calcium powder and the water glass, uniformly mixing and calcining, adding the polyvinyl alcohol solution for primary ultrasonic dispersion, adding the polydimethylsiloxane, the calcium sulfate whisker and the silane coupling agent for secondary ultrasonic dispersion, drying and grinding to obtain the iron ore tailing mud-based cement admixture. According to the method, the iron ore tailing mud waste obtained after beneficiation serves as the raw material and is pretreated to be used for preparing the cement-based mixed material, the comprehensive utilization rate of the waste can be increased, resources are saved, the doping amount of the iron ore tailings pretreated through the method can be increased, meanwhile, the influence of the iron ore tailings on cement performance can be reduced, and the cement-based mixed material is obtained. The cement has good compressive strength and breaking strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of iron ore tailings, and in particular to an iron ore tailings-based cement admixture and a preparation method thereof. Background Art

[0002] Iron ore tailings are waste after ore dressing, and are also the main component of common industrial solid waste. Iron ore tailings are mainly composed of finely divided ores, sulfides, clays and various heavy metal elements. Due to the characteristics of small particle size and high water content, iron ore tailings are easily eroded by Feng Shui under natural conditions, resulting in environmental pollution and waste of resources. The dissolution of harmful substances in the tailings will also have a serious impact on nearby water bodies and soil. Traditional iron ore tailings treatment usually stores them in the form of tailings dams, which can reduce pollution to the environment. However, with the increase in the number of tailings, the safety risk of tailings dams is gradually increasing, and the storage of tailings dams also requires a large amount of land resources, which invisibly increases the occupation of the environment and the potential pollution. Therefore, it is necessary to find a method for harmless treatment of iron ore tailings while improving the efficient utilization of resources. With the rise of more and more buildings, the demand for building materials is also increasing. Iron ore tailings contain substances such as potassium feldspar, calcite, and other silicates, which are conducive to using them in the preparation of cement mixtures, thereby effectively improving the utilization of iron ore tailings. Summary of the invention

[0003] In view of this, the present invention provides an iron ore tailings-based cement admixture and a preparation method thereof.

[0004] The technical solution of the present invention is achieved in this way:

[0005] An iron ore tailings-based cement admixture comprises the following raw materials in parts by weight: 50-60 parts of iron ore tailings, 12-16 parts of composite calcium powder, 8-13 parts of water glass, 18-25 parts of polyvinyl alcohol solution, 10-14 parts of polydimethylsiloxane, 20-27 parts of calcium sulfate whiskers and 12-16 parts of silane coupling agent.

[0006] Furthermore, the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 1 to 3:1.

[0007] Furthermore, the concentration of the polyvinyl alcohol solution is 70-80 wt%.

[0008] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing it to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, calcining the mixture and then cooling and crushing it, then adding it to a polyvinyl alcohol solution for a first ultrasonic dispersion, then adding polydimethylsiloxane, calcium sulfate whiskers and silane coupling agent for a second ultrasonic dispersion, drying and grinding to obtain the iron ore tailing mud-based cement admixture.

[0009] Furthermore, the calcination process is to heat up to 500-600° C. at a rate of 5-6° C. / min and keep the temperature for 60-90 min, then heat up to 800-1000° C. at a rate of 8-10° C. / min and keep the temperature for 12-15 min.

[0010] Furthermore, the primary ultrasonic power is 200-300W, the rotation speed is 400-500r / min, and the time is 7-9min.

[0011] Furthermore, the secondary ultrasonic power is 500-600W, the rotation speed is 600-800r / min, and the time is 12-15min.

[0012] Furthermore, the grinding speed is 1000-1200 r / min and the grinding time is 10-20 min.

[0013] Furthermore, after grinding, the fineness of the pretreated iron ore tailings is ≤60 μm.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The present invention uses iron ore tailings waste after ore dressing as raw material, pre-treats it and uses it to prepare cement-based admixtures, which can improve the comprehensive utilization rate of waste and save resources. When the iron ore tailings treated by the method of the present invention are used to prepare cement, while increasing its dosage, it can also reduce its influence on cement performance, so that the cement has good compressive strength and flexural strength.

[0016] Specifically, in the process of pre-treating the iron ore tailings, the present invention mixes the iron ore tailings with composite calcium powder and water glass and then calcines them at a preferred temperature, which can improve the activity of the iron ore tailings and allow the iron ore tailings to form a stable mineral phase. The calcined iron ore tailings are then subjected to secondary ultrasonic dispersion with polyvinyl alcohol, polydimethylsiloxane, and calcium sulfate whiskers under suitable conditions, which can allow the iron ore tailings to be fully mixed with materials such as calcium sulfate whiskers to fill the gaps in each part to increase the density and strength, and can also improve the dispersibility of the iron ore tailings in cement to avoid agglomeration, and can also improve the bonding performance of the iron ore tailings with other materials in cement, thereby effectively improving the performance of the cement. DETAILED DESCRIPTION

[0017] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0018] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0019] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0020] Example 1

[0021] An iron ore tailings-based cement admixture comprises the following raw materials in parts by weight: 50 parts of iron ore tailings, 16 parts of composite calcium powder, 13 parts of water glass, 23 parts of polyvinyl alcohol solution, 12 parts of polydimethylsiloxane, 23 parts of calcium sulfate whiskers, and 14 parts of silane coupling agent; the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 1:1; the concentration of the polyvinyl alcohol solution is 70wt%;

[0022] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing it to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, heating the mixture to 600°C at a rate of 6°C / min and keeping the temperature for 90 minutes, then heating the mixture to 800°C at a rate of 8°C / min and keeping the temperature for 12 minutes, calcining, cooling and crushing it, then adding it to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 9 minutes at a power of 200W and a rotation speed of 500r / min, then adding polydimethylsiloxane, calcium sulfate whisker and silane coupling agent and performing a secondary ultrasonic dispersion for 12 minutes at a power of 600W and a rotation speed of 800r / min, drying it, and finally grinding it at a rotation speed of 1200r / min for 20 minutes to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0023] Example 2

[0024] An iron ore tailings-based cement admixture comprises the following raw materials in parts by weight: 60 parts of iron ore tailings, 12 parts of composite calcium powder, 8 parts of water glass, 18 parts of polyvinyl alcohol solution, 14 parts of polydimethylsiloxane, 20 parts of calcium sulfate whiskers, and 15 parts of silane coupling agent; the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 3:1; the concentration of the polyvinyl alcohol solution is 80wt%;

[0025] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing the iron ore tailing mud to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, heating the mixture to 500°C at a rate of 5°C / min and keeping the temperature for 60 minutes, then heating the mixture to 900°C at a rate of 10°C / min and keeping the temperature for 13 minutes, then cooling and crushing the mixture, then adding the mixture to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 7 minutes at a power of 300W and a rotation speed of 400r / min, then adding polydimethylsiloxane, calcium sulfate whiskers and silane coupling agent and performing a secondary ultrasonic dispersion for 13 minutes at a power of 550W and a rotation speed of 700r / min, drying, and finally grinding the mixture at a rotation speed of 1100r / min for 10 minutes to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0026] Example 3

[0027] An iron ore tailings-based cement admixture comprises the following raw materials in parts by weight: 54 parts of iron ore tailings, 14 parts of composite calcium powder, 10 parts of water glass, 20 parts of polyvinyl alcohol solution, 10 parts of polydimethylsiloxane, 24 parts of calcium sulfate whiskers, and 16 parts of silane coupling agent; the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 2:1; the concentration of the polyvinyl alcohol solution is 75wt%;

[0028] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing the iron ore tailing mud to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, heating the mixture to 550°C at a rate of 6°C / min and keeping the temperature for 70 minutes, then heating the mixture to 1000°C at a rate of 9°C / min and keeping the temperature for 14 minutes, then cooling and crushing the mixture, then adding the mixture to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 8 minutes at a power of 250W and a rotation speed of 400r / min, then adding polydimethylsiloxane, calcium sulfate whisker and silane coupling agent and performing a secondary ultrasonic dispersion for 15 minutes at a power of 500W and a rotation speed of 600r / min, drying, and finally grinding the mixture at a rotation speed of 1000r / min for 13 minutes to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0029] Example 4

[0030] An iron ore tailings-based cement admixture comprises the following raw materials in parts by weight: 58 parts of iron ore tailings, 15 parts of composite calcium powder, 12 parts of water glass, 25 parts of polyvinyl alcohol solution, 13 parts of polydimethylsiloxane, 27 parts of calcium sulfate whiskers, and 13 parts of silane coupling agent; the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 2:1; the concentration of the polyvinyl alcohol solution is 75wt%;

[0031] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing the iron ore tailing mud to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, heating the mixture to 500°C at a rate of 5°C / min and keeping the temperature for 80 minutes, then heating the mixture to 1000°C at a rate of 10°C / min and keeping the temperature for 15 minutes, then cooling and crushing the mixture, then adding the mixture to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 8 minutes at a power of 200W and a rotation speed of 500r / min, then adding polydimethylsiloxane, calcium sulfate whisker and silane coupling agent and performing a secondary ultrasonic dispersion for 12 minutes at a power of 600W and a rotation speed of 700r / min, drying, and finally grinding the mixture at a rotation speed of 1200r / min for 15 minutes to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0032] Comparative Example 1

[0033] The difference between this comparative example and Example 4 is that the raw material ratio of the iron ore tailings-based cement admixture is changed, and the rest is the same as Example 4. The iron ore tailings-based cement admixture of this comparative example includes the following raw materials in parts by weight: 58 parts of iron ore tailings, 8 parts of composite calcium powder, 7 parts of water glass, 46 parts of polyvinyl alcohol solution, 25 parts of polydimethylsiloxane, 12 parts of calcium sulfate whiskers, and 7 parts of silane coupling agent.

[0034] Comparative Example 2

[0035] The difference between this comparative example and Example 4 is that the iron ore tailings-based cement admixture does not contain composite calcium powder and water glass, and the rest is the same as Example 4.

[0036] The iron ore tailings-based cement admixture of this comparative example comprises the following raw materials in parts by weight: 70 parts of iron ore tailings, 30 parts of polyvinyl alcohol solution, 18 parts of polydimethylsiloxane, 27 parts of calcium sulfate whiskers, and 18 parts of silane coupling agent; the concentration of the polyvinyl alcohol solution is 75wt%;

[0037] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing it to obtain crushed iron ore tailing mud, heating it to 500°C at a rate of 5°C / min and keeping it warm for 80 minutes, then heating it to 1000°C at a rate of 10°C / min and keeping it warm for 15 minutes, then cooling and crushing it, then adding it to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 8 minutes at a power of 200W and a rotation speed of 500r / min, then adding polydimethylsiloxane, calcium sulfate whiskers and silane coupling agent and performing a secondary ultrasonic dispersion for 12 minutes at a power of 600W and a rotation speed of 700r / min, drying it, and finally grinding it at a rotation speed of 1200r / min for 15 minutes, so as to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0038] Comparative Example 3

[0039] The difference between this comparative example and Example 4 is that the iron ore tailings-based cement admixture does not contain polydimethylsiloxane and calcium sulfate whiskers, and the rest is the same as Example 4.

[0040] The iron ore tailings-based cement admixture of this comparative example comprises the following raw materials in parts by weight: 71 parts of iron ore tailings, 22 parts of composite calcium powder, 17 parts of water glass, 35 parts of polyvinyl alcohol solution, and 18 parts of silane coupling agent; the composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 2:1; the concentration of the polyvinyl alcohol solution is 75wt%;

[0041] The preparation method of the iron ore tailing mud-based cement admixture comprises the following steps: drying the iron ore tailing mud to a water content of ≤1% and then crushing the iron ore tailing mud to obtain crushed iron ore tailing mud, adding composite calcium powder and water glass to mix well to obtain a mixture, heating the mixture to 500°C at a rate of 5°C / min and keeping the temperature for 80 minutes, then heating the mixture to 1000°C at a rate of 10°C / min and keeping the temperature for 15 minutes, then cooling and crushing the mixture, then adding the mixture to a polyvinyl alcohol solution and performing an ultrasonic dispersion for 8 minutes at a power of 200W and a rotation speed of 500r / min, then adding a silane coupling agent and performing a secondary ultrasonic dispersion for 12 minutes at a power of 600W and a rotation speed of 700r / min, drying, and finally grinding the mixture at a rotation speed of 1200r / min for 15 minutes to obtain the iron ore tailing mud-based cement admixture with a fineness of ≤60μm.

[0042] Comparative Example 4

[0043] The difference between this comparative example and Example 4 is that the conditions of ultrasonic dispersion are changed, and the rest are the same as Example 4.

[0044] The preparation method of the iron ore tailings-based cement admixture of the comparative example comprises the following steps: drying the iron ore tailings to a water content of ≤1% and then crushing to obtain crushed iron ore tailings, adding composite calcium powder and water glass and mixing to obtain a mixture, heating the mixture to 500°C at a rate of 5°C / min and keeping the temperature for 80min, then heating the mixture to 1000°C at a rate of 10°C / min and keeping the temperature for 15min, calcining the mixture, cooling and crushing the mixture, then adding polyvinyl alcohol solution, polydimethylsiloxane, calcium sulfate whisker and silane coupling agent and ultrasonically dispersing the mixture at a power of 200W and a rotation speed of 400r / min for 20min, drying, and finally grinding the mixture at a rotation speed of 1200r / min for 15min to obtain an iron ore tailings-based cement admixture with a fineness of ≤60μm.

[0045] The iron ore tailings-based cement admixture prepared in the above Examples 1-4 and Comparative Examples 1-4 was mixed with silicate cement clinker to prepare silicate cement, and the properties of the prepared silicate cement were measured. The mass percentages of the iron ore tailings-based cement admixture, silicate cement clinker, and desulfurized gypsum in the silicate cement raw materials were 40%, 55%, and 5%, respectively. The properties of the prepared silicate cement were measured according to GB175-2023, and the results are shown in Table 1 below.

[0046] Table 1 Properties of Portland cement mixed with iron ore tailings-based cement admixtures

[0047]

[0048]

[0049] The above results show that the iron ore tailings-based cement admixture obtained by the suitable raw material ratio and the suitable preparation method of the present invention can make the silicate cement have good mechanical properties after being mixed with silicate cement clinker, and the 28-day flexural strength is 10.49-11.05MPa, and the 28-day compressive strength is 52.36-53.27MPa. Compared with Example 4 of the present invention, Comparative Example 1 changes the raw material ratio of the iron ore tailings-based cement admixture, and Comparative Example 2 does not contain composite calcium powder and water glass when the iron ore tailings are calcined, and Comparative Example 3 does not contain polydimethylsiloxane and calcium sulfate whiskers, which affect the performance of the iron ore tailings during the preparation process, resulting in the influence of the mechanical properties of silicate cement after the preparation of silicate cement, so that the flexural strength and compressive strength of silicate cement are reduced. Compared with Example 4, Comparative Example 4 changes the price adjustment of ultrasonic dispersion, resulting in the iron ore tailings and calcium sulfate whiskers not being well mixed and filled, affecting the performance of silicate cement.

[0050] In addition, the iron ore tailings-based cement admixture prepared in Examples 1-4 of the present invention was added to silicate cement at a dosage of 50%, and the silicate cement prepared also had good performance.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An iron ore tailings-based cement admixture, characterized in that: The invention comprises the following raw materials in parts by weight: 50-60 parts of iron ore tailings, 12-16 parts of composite calcium powder, 8-13 parts of water glass, 18-25 parts of polyvinyl alcohol solution, 10-14 parts of polydimethylsiloxane, 20-27 parts of calcium sulfate whiskers and 12-16 parts of silane coupling agent.

2. The iron ore tailings-based cement admixture according to claim 1, characterized in that: The composite calcium powder comprises calcium oxide and calcium hydroxide in a mass ratio of 1 to 3:

1.

3. The iron ore tailings-based cement admixture according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution is 70-80 wt %.

4. The method for preparing the iron ore tailings-based cement admixture according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: drying iron ore tailings to a water content of ≤1% and then crushing the iron ore tailings to obtain crushed iron ore tailings; adding composite calcium powder and water glass to mix well to obtain a mixture; calcining the mixture and then cooling and crushing the mixture; then adding the mixture to a polyvinyl alcohol solution for a first ultrasonic dispersion; then adding polydimethylsiloxane, calcium sulfate whiskers and a silane coupling agent for a second ultrasonic dispersion; drying and grinding to obtain an iron ore tailings-based cement mixture.

5. The method for preparing the iron ore tailings-based cement admixture according to claim 4, characterized in that: The calcination process is to heat up to 500-600°C at a rate of 5-6°C / min and keep the temperature for 60-90min, then heat up to 800-1000°C at a rate of 8-10°C / min and keep the temperature for 12-15min.

6. The method for preparing the iron ore tailings-based cement admixture according to claim 4, characterized in that: The primary ultrasonic power is 200-300W, the rotation speed is 400-500r / min, and the time is 7-9min.

7. The method for preparing the iron ore tailings-based cement admixture according to claim 4, characterized in that: The secondary ultrasonic power is 500-600W, the rotation speed is 600-800r / min, and the time is 12-15min.

8. The method for preparing the iron ore tailings-based cement admixture according to claim 4, characterized in that: The grinding speed is 1000-1200 r / min, and the grinding time is 10-20 min.

9. The method for preparing the iron ore tailings-based cement admixture according to claim 4, characterized in that: After grinding, the fineness of the pretreated iron ore tailings is ≤60μm.

Citation Information

Patent Citations

  • Preparation method for Portland cement with iron tailings

    CN104150794A

  • Green composite cement and preparation method thereof

    CN107129166A

  • Lightweight heat-resistant milltailings hollow brick and preparation thereof

    CN107140915A

  • Concrete mortar and preparation method thereof

    CN111848039A

  • Environmentally-friendly composite quick-drying high-performance concrete

    CN111978042A